Translational control by the DEAD Box RNA helicase belle regulates ecdysone-triggered transcriptional cascades. - Robert J Ihry; Anne L Sapiro; Arash Bashirullah (PLoS Genetics)
Steroid hormones act, through their respective nuclear receptors, to regulate target gene expression. Despite their critical role in development, physiology, and disease, however, it is still unclear how these systemic cues are refined into tissue-specific responses. We identified a mutation in the evolutionarily conserved DEAD box RNA helicase belle/DDX3 that disrupts a subset of responses to the steroid hormone ecdysone during Drosophila melanogaster metamorphosis. We demonstrate that belle directly regulates translation of E74A, an ets transcription factor and critical component of the ecdysone-induced transcriptional cascade. Although E74A mRNA accumulates to abnormally high levels in belle mutant tissues, no E74A protein is detectable, resulting in misregulation of E74A-dependent ecdysone response genes. The accumulation of E74A mRNA in belle mutant salivary glands is a result of auto-regulation, fulfilling a prediction made by Ashburner nearly 40 years ago. In this model, Ashburner postulates that, in addition to regulating secondary response genes, protein products of primary response genes like E74A also inhibit their own ecdysone-induced transcription. Moreover, although ecdysone-triggered transcription of E74A appears to be ubiquitous during metamorphosis, belle-dependent translation of E74A mRNA is spatially restricted. These results demonstrate that translational control plays a critical, and previously unknown, role in refining transcriptional responses to the steroid hormone ecdysone.